Street Diplomacy : The Politics of Slavery and Freedom in Philadelphia, 1820-1850 - Drago, Elliott, 1984- (Book collections on Project MUSE., 2022)
Studying these timely struggles over race, politics, enslavement, and freedom in Philadelphia will encourage scholars to reexamine how Black freedom was not secure in Pennsylvania or in the wider United States.